Synchronous fluvial response to surface uplift in the eastern Tibetan Plateau: Implications for crustal dynamics. Issue 1 (12th January 2015) - Tian, Yuntao; Kohn, Barry P.; Hu, Shengbiao; Gleadow, Andrew J. W.
Abstract Synchronous response of river erosion to surface uplift is often assumed by studies using thermochronometer‐constrained erosion histories to estimate changes in landscape and tectonics. We have tested this assumption by studying river incision histories at two sites (Heishui and Lianghekou) located in the westernmost inland part of the deeply incised eastern Tibetan Plateau. Apatite fission track age‐elevation plots for the two sites show clear late Miocene inflection points, marking the time when apparent erosion rates increased fourfold to eightfold to 300–800 m/Myr. This timing is further refined as 10–12 Ma by thermal history modeling and overlaps within analytical uncertainties with that recorded from the eastern Tibetan Plateau margin 150–200 km to the east, demonstrating that river incision propagated rapidly from the margin to the interior in less than 2 Ma. Such synchronous regional river incision is consistent with regional surface uplift generated by crustal extrusion along a detachment at depth.